Diversifying Doulas Initiative: Improving Maternal Health Outcomes in People of Color Through Doula Care - Sharee Livingston; Cherise Hamblin; Crista Johnson; LaShekia Chatman; Kayla Bolden (Health Equity)
The Diversifying Doulas Initiative (DDI) aims to improve maternal health outcomes in Black and Brown people through doula care in Lancaster County. DDI trained 28 Black and Brown doulas and provided fully subsidized doula care to over 200 patients of color giving birth in Lancaster County. The perinatal workforce comprises community birth workers, doulas, midwives, nurses, students, and physicians. By diversifying the perinatal workforce and increasing access to doulas, patients of color benefit from a proven intervention.